Research on Various Cryptography Techniques - Bharati A. Patil,; Prajakta R. Toke,; Sharyu S. Naiknavare, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cryptography is utilized to make secure data transmission over networks. The algorithm called for cryptography should meet the conditions of authentication, confidentiality, integrity and non-repudiation. Cryptography is a technique used from decenniums to secure and forfend the information and send the data from one place to another without the trepidation of having been read out by some unauthorized and unauthenticated denotes. Several ways has been developed in this field to make the information more secure and evade trespassing. However these methods may have some loopholes or shortcoming which leads to the leakage of information and thus raising a question of information security. The cryptographic technique is utilized not only to provide the security but additionally it deals with data integrity, confidentiality and non-repudiation issues. To safeguard data during transmission or storage, sundry algorithms and methods have been developed in the field of security. A wide range of cryptography approaches are employed, each with its own set of strengths and inhibitions that are acclimated to provide data security. Cryptography can be defined as techniques that cipher data, depending on categorical algorithms that make the data unreadable to the human ocular perceiver unless decrypted by algorithms that are predefined by the sender. It encrypts data utilizing a set of algorithms such as symmetric and asymmetric algorithms. These encryption methods vary in terms of vitality, celerity, and utilization of resources (CPU utilization, recollection, and power). It is utilized to bulwark personal identifiable information (PII) and other confidential data, authenticate identities, avert document tampering, and build trust between servers. Cryptography is one of the most paramount techniques utilized by digital businesses to safeguard the systems that store their most valuable asset – data – whether it is at rest or in kinetic Customer PII, employee PII, perspicacious property, company strategies, and any other confidential information are examples of data. As a result, cryptography is a vital infrastructure, as the aegis of sensitive data increasingly relies on cryptographic solutions. In this paper I have discussed various cryptographic techniques and the inhibitions of those techniques as well. Some cryptographic algorithms are briefly described and their impact on the information is additionally mentioned.
Keywords: Cryptography; Information Security; Encryption; Decryption; Symmetric Cryptography; Asymmetric Cryptography Private Key; Public Key